Investigation on the Mechanical Behavior of Passively Confined Cementitious Treated Sand - Laras Laila Lestari; Bambang Piscesa; Priyo Suprobo; Yudhi Lastiasih (Civil Engineering Journal, 2026)
This study aims to develop a practical and accessible approach for evaluating the mechanical behavior of Cementitious Treated Sand (CTS) under passive confinement using Glass Fiber Reinforced Polymer (GFRP) wraps. A method utilizing three GFRP layer configurations was applied to investigate the confinement effect and assess the role of confining stiffness. Path-dependency was analyzed through derived confining pressure rates, and Mohr-Coulomb failure analysis was used to determine shear-strength parameters. Analysis of plastic volumetric behavior revealed that after an initial elastic state, the material dilates upon yielding—activating the confinement mechanism—before recompacting under sufficient confining pressure due to pore structure collapse. Results indicate that the proposed novel constitutive model successfully predicts both axial and lateral stress-strain responses. It accurately represents the nonlinear stress-strain relationship, the transition in volumetric behavior, and the interaction between axial and lateral strains through the proposed dilation formulation. The model incorporates a plastic dilation rate model to capture the dilation-to-compaction transition and demonstrates excellent agreement with experimental results across all confinement levels. This framework provides a reliable analytical tool for designing soil stabilization schemes using passive confinement, offering engineers a practical alternative to conventional geotechnical analysis while enhancing reproducibility, sustainability, and applicability across diverse construction projects.